Concentrations of Polycyclic Aromatic Hydrocarbons in Indian Atmosphere During 1999-2011 - Narayana Suvarapu, Lakshmi; Seo, Young-Kyo; Baek, Sung-Ok (Asian Journal of Chemistry, 2012)
India is the seventh largest country by geographical area and the second highest populous country with over 1.2 billion people in the world. India is one of the fastest growing major economies in the world, because of the economic reforms introduced in 1991. In this paper, we reviewed and discussed the concentration of PAHs have been reported in India during 1999-2011.